Razer / Ammar Adnan - Adnan, Ammar (2022)
The goal of this project is to figure out what the product's flaw is. Razer is the company that I have selected. I chose the Razer Phone 2 as the subject of my investigation from their wide range of devices. In this case study, I used a SWOT analysis to determine the Razer phone 2's strengths, weaknesses, opportunities, and threats. The camera is the primary issue I found with this Razer Phone 2. I believe the greatest option is to remove the camera from the Razer Phone 2, which is one of the first gaming phones to prioritise phone performance while playing games or watching movies.